Atomistic simulation of influence of laser nano-structured diamond abrasive on the polishing behavior of silicon. (January 2020) - Dai, Houfu; Zhou, Yuqi; Zhang, Fa
Abstract: Micro/nano-structured surfaces often present many interesting behaviors and lend themselves to advanced functions. To further improve the polishing performance of diamond abrasives, large scale MD (molecular dynamics) simulations are employed to investigate the ultra-precision mechanical polishing of monocrystalline silicon with laser-fabricated nano-structured diamond abrasive. The material removal mechanism during polishing using structured diamond abrasive is studied in detail. The effects of the structured depth, structured width, structured factor, and structured pattern on the material deformation are studied in detail by analyzing the surface morphologies of the polished surface, normal stresses, shear stress, polishing temperature, atomic coordination numbers, von Mises stress, hydrostatic stress, polishing force, and dislocation extraction algorithm (DXA). The simulation results show that a bigger structured width abrasive, smaller structured depth abrasive，higher structured factor abrasive, or rectangle pattern abrasive would cause a larger material removal rate. Moreover, the abrasive with a smaller structured width, smaller structured depth, or higher structured factor tends to polish silicon materials in a more ductile mode. The abrasive with a bigger structured width has a lower hydrostatic stress, better polished surface, and less defect atoms. However, the abrasive with a bigger structured width, smaller structured depth, or higher structured factor results in a larger normal polishing force. Polishing using an abrasive with a higher structured factor leads to more polishing heat. In addition, the abrasive with 33.3% structured factor polishing can reduce the tangential polishing forces.